GPU CUDA accelerated Image Inpainting using Fourth Order PDE equation - Edwin Prananta; Pranowo Pranowo; Djoko Budianto (Universitas Ahmad Dahlan, 2016)
This paper describes the technique to accelerate inpainting process using fourth order PDE equation using GPU CUDA. Inpainting is the process of filling in missing parts of damaged images based on information gleaned from surrounding areas. It uses the GPU computation advantage to process PDE equation into parallel process. Fourth order PDE will be solved using parallel computation in GPU. This method can speed up the computation time up to 36x using NVDIA GEFORCE GTX 670.